Fontes de fósforo e torta de filtro sobre o estado nutricional e produtividade da cana-planta - Vasconcelos, Ricardo de Lima [UNESP] (2013)
Proper management of phosphorus is important in cane sugar and may interfere with the whole development of culture, raising therefore the economic returns to its cultivation. This study aimed to evaluate the effect of sources of phosphorus and filter cake on the cane, from assessments of P content in soil and plant P, accumulation in leaves, stalks and canopy (leaf and stalk), gas exchange, acid phosphatase stalk production. The experiment was conducted on a Dystrophic Red Yellow Latosoil, medium texture, in the city of Itajobi-SP. The experimental design was a randomized block design with three replications in a factorial 3x4x2 with three phosphorus sources (triple superphosphate, natural Bayóvar reactive phosphate and natural Araxá phosphate), four doses (0, 90, 180 and 360 kg of P2O5 ha-1) in the absence and in the presence of filter cake (7,5 t ha-1, dry basis). The effect of increasing doses of phosphorus in the P content in soil, leaf, accumulation in the plant stands out in the presence of the filter cake in relation your absence. However, the use of filter cake without phosphorus was sufficient to provide the highest stalks yield of sugarcane. The use of higher dose of triple superphosphate or the combination of the filter cake with this source provided the greatest reductions in acid phosphatase activity. The use of higher dose of phosphorus increased the activity of photosynthesis, stomatal conductance and transpiration in plants of cane sugar